Sustainability based on indigenous materials of building construction - Vandna Sharma (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2020)
Construction of shelter is one of the basic and prime needs of human civilization. With the passage of time, the basic of construction of this shelter have evolved from simple caves to magnificent houses, palaces and like. Similar is the case with building materials and construction industry that has evolved from the use of simple straw, mud, thatch, and slates to modern day conventional building material like bricks, reinforced cement concrete, tiles, glass, steel, prefabricated materials and many more. As per research studies by the Shukla et al.